Residues of sweet sorghum promotes suppression of weeds in sugarcane rotation - Giancotti, Paulo Roberto Fidelis; Nepomuceno, Mariluce Pascoína [UNESP]; de Souza Rodrigues, Juliana [UNESP]; Yamauti, Micheli [UNESP]; Martins, José Valcir Fidelis [UNESP]; da Costa Aguiar Alves, Pedro Luís [UNESP] (Southern Cross Publishing, 2020)
Sorghum is an important crop to plant in rotation with sugarcane. This is mainly because both are inputs for the ethanol industry. Crop residues of sweet sorghum promote suppression of weed re-infestation, avoiding weed interference to the sugarcane crop due to the strong allelopathic potential of sorghum. In order to determine the suppressive effects of sorghum crop residues on weeds, a field experiment was carried out. Seven vegetation covers were used as options for crop rotation with sugarcane. The treatments were sweet sorghum, velvet bean, sunflower, soybean, sugar cane, fallow, and an area without cover. The experiment was randomized blocks with four replications of 27 m2 plots. The weed community of each plot was evaluated by phytosociological indexes at 60 and 120 days after the formation of vegetation cover. The composition of soil seed bank was also evaluated. The weeds with the highest indexes of relative importance during the evaluations were Cyperus rotundus, Raphanus raphanistrum and Parthenium hysterophorus. The diversity of the weed community, estimated by relative importance indexes, was lower in the area with velvet bean as soil cover. Sorghum, velvet bean and sunn hemp covers reduced the soil seed bank compared to the fallow treatment and the treatment without vegetation cover. Crop residues of sweet sorghum and velvet bean provide a decrease in weed infestation in field, and the weed suppression period can last up to 120 days during the dry season.